Catalase, superoxide dismutase, and virulence of Staphylococcus aureus. In vitro and in vivo studies with emphasis on staphylococcal--leukocyte interaction. - Mandell, G L (1975)
Since oxygen-free polymorphonuclear neutrophils (PMN) cannot kill Staphylococcus aureus normally, the usual mechanisms for PMN bactericidal activity probably involve hydrogen peroxide or superoxide. Catalase can destroy hydrogen peroxide, and superoxide dismutase breaks down superoxide. Experiments were performed to study the influence of these enzymes (which are found in staphylococci) on virulence for mice or on leukocyte-bacterial interaction. 15 staphylococcal strains were injected i.p. into mice to quantitate virulence. There was good correlation between staphylococcal catalase activity and mouse lethality (r equals 0.88) but no correlation between staphylococcal superoxide dismutase activity and mouse lethality (r equals 0.14). Exogenous catalase (10,000 U/ml) increased the virulence of low-catalase staphylococci, but exogenous superoxide dismutase (200 mug/ml) did not alter the virulence of staphyloccal strains. C14=labeled high-catalase or low-catalase staphylococci were ingested equally well by PMN, with or without the addition of exogenous catalase. A high-catalase staphylococcal strain was killed relatively poorly by PMN, and addition of exogenous catalase (but not superoxide dismutase) decreased the ability of PMN to kill a low-catalase strain. Iodination of bacterial proteins by PMN is related to hydrogen peroxide, and a high-catalase staphylococcal strain was iodinated only 63% as much as a low-catalase strain. Addition of exogenous catalase decreased iodination of the low-catalase strain by 23%. These findings suggest that staphylococcal catalase protects intraphagocytic microbes by destroying hydrogen peroxide produced by the phagocyte. Thus, catalase may be a significant staphylococcal virulence factor.